Out of business and on budget the challenge of military financing in Indonesia - Rieffel, Alexis, 1941-; Pramodhawardani, Jaleswari; ebrary, Inc. (Washington, D.C. : United States-Indonesia Society : Brookings Institution Press, 2007)
"Describes the evolution of the military's business empire and its decline after 1998. Examines what is necessary to bring the Indonesian military "on-budget": what policies are required, what Indonesia can learn from other nations, and what a realistic timetable looks like"--Provided by publisher.
Policy objectives : out of business and on budget -- Policy context : external and internal factors -- The legacies of Sukarno and Suharto and the shock of Reformasi -- The TNI's current business activities -- The TNI's off-budget revenues and expenditures -- From starting point to finish line -- Designing a national defense and security strategy -- Budget realities -- Observations and implications -- Appendixes. A brief history of the TNI and its current structure ; Methodology for estimating the gross revenue and net income of the TNI's off-budget activities.
Includes bibliographical references (p. 135-139) and index.
Electronic reproduction.
Keywords: Indonesia. -- Tentara Nasional; National security -- Economic aspects -- Indonesia; National security -- Indonesia; Indonesia -- Economic policy; Indonesia -- Military policy; Electronic books